Hemlock loss due to the hemlock woolly adelgid does not affect ecosystem C storage but alters its distribution. Issue 5 (29th May 2013) - Raymer, Poliana C. L.; Orwig, David A.; Finzi, Adrien C.
Abstract : The 1950s introduction of the hemlock woolly adelgid (HWA, Adelges tsugae ) has caused extensive hemlock ( Tsuga canadensis ) mortality with little understanding of the long‐term consequences for forest carbon (C) storage. In southern New England, hemlock is being replaced by the early successional species black birch ( Betula lenta ). The objective of this research was to measure C stocks in stand types of varying age and abundance of hemlock and/or black birch. Using information from previous studies and comparisons of data between plots with identical land‐use history, we addressed the question of whether the quantity and distribution of C pools in black birch forests are the same as those found in the hemlock stands they replace and, if so, over what time scales. If HWA did not infest hemlock stands in central MA, C stocks in these secondary stands could still increase by at least ∼30% over a period of 100 years. Girdling, intended to simulate HWA infestation, resulted in a large transfer of C from live biomass to coarse woody debris five years after treatment, but had little effect on total ecosystem C content. A former hemlock stand killed by HWA and now dominated by black birch saplings (∼23, 000 stems ha −1 ) also had a large pool of highly decayed CWD and a rapidly aggrading C pool in live biomass. C pools in biomass in a mature, secondary growth black birch stand ∼135 years since pastureland abandonment were as large as those in a primary‐growth hemlock stand ∼235 years of age. Because of uncertainties in the intensity of former land use and time since pastureland abandonment, this analysis can only speak to the potential consequences of HWA on forest‐C balance over the long term. Based on this analysis, it appears that ecosystem C storage is resilient to the loss of hemlock because of vigorous regrowth by black birch. This empirical finding is consistent with the results of a recent modeling effort.